Botswana : Technical Assistance Report-Price Statistics. (IMF Staff Country Reports; Country Report, 2022)
A technical assistance (TA) mission was conducted by the International Monetary Fund's (IMF) Regional Technical Assistance Center for Southern Africa (AFS)1 during November 22-26, 2021 to continue assisting Statistics Botswana (SB) with developing the producer price index (PPI). Due to ongoing COVID-19 related travel restrictions, this mission was conducted remotely using Microsoft Teams, WhatsApp, and email. Previous missions to assist with developing price indexes were held in February 2019 and October 2020.